FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI JAGUNG DI DESA HUIDU KECAMATAN LIMBOTO BARAT KABUPATEN GORONTALO - Ramlah Alkatiri; Samin Imran (Universitas Muhammadiyah Gorontalo, 2023)
This study aims to determine what factors affect the income of corn farmers in Huidu Village, West Limboto District, Gorontalo Regency. This study used a quantitative research approach using a questionnaire research instrument. Source of data used comes from 37 respondents. The factors that affect the income of corn farmers (Y) and the factors that influence it consist of X1 = price, X2 = labor, and X3 = fertilizer price. The analytical tool used is multiple linear regression. The results showed that Labor, Fertilizers, and Corn Selling Prices on Corn Farmers' Income in Huidu Village, Limboto Barat District, Gorontalo Regency, based on the results of partial analysis, were in fact from 3 factors that affected income. Only two factors have the most influence, namely the price of fertilizer and the selling price of corn, while the labor factor has no significant effect. This is because the results of the calculation of 0.823 significance value is greater than α 0.05. Income of Corn Farmers in Huidu Village, West Limboto District, based on the results of a simultaneous analysis (together), it turns out that the 3 factors (Labor, Fertilizer, and Selling Price) have a significant effect on the income of corn farmers. This is because the results of the calculation of F = 0.002 (smaller than α = 0.05) in the simultaneous test (F test). Overall, the income of corn farmers in Huidu Village, West Limboto District, Gorontalo Regency, is influenced by labor factors, fertilizer prices, and selling prices.